George Strong Nares (1831-1915) - Deacon, Margaret (ARCTIC, 1985)
. In 1852 Nares sailed for the Arctic in the Resolute, under Captain Henry Kellet. The Resolute and the Intrepid wintered off Melville Island, and Nares took part in sledge journeys searching unavailingly for traces of the missing ships. Instead they found a message that led to the rescue of McClure and the crew of the Investigator, frozen in off Banks Island after passing through the Bering Strait. . The British Arctic Expedition of 1875-1876, in H.M. Ships Alert and Discovery, was inspired by the recurring myth of an open polar sea. They attempted to reach the North Pole by sailing into the Arctic Ocean via Smith Sound, separating Greenland from Ellesmere Island. This proved impossible, but the Alert succeeded in reaching Floeberg Beach, in 82 degrees North, on the northeast tip of Ellesmere Island. The following spring, sledging parties set out to explore the nearby lands and to attempt to reach the North Pole over the ice. Disaster struck when an outbreak of scurvy led to several deaths. . In the enquiry that followed, Nares was blamed for the outbreak through not ensuring that lime juice was carried on the sledges. It had sometimes been omitted because of the difficulties in storing and administering it at sub-zero temperatures. . In the 1850s he had foreseen how future expeditions could be made less arduous by using dogs to replace backpacking or man-hauled sledges, but the snow and ice conditions encountered by the 1875-1976 expedition were very different from those experienced farther south in the Canadian Arctic Archipelago. Their old-fashioned heavy equipment did not help, and dogs were of little use. However, their achievement and the seamanship on which it relied were recognised when Nares was given a knighthood on his return. .